An Embedded Real-Time Traffic Simulation Environment on Vehicle-In-Loop Framework for Autonomous Driving - CHANDRASHEKAR, VARSHA; WANG, XINYUAN (My University, 2021)
Autonomous driving(AD) and Advanced Driver Assistance (ADAS) functions are rapidly evolving. Extensive testing of these systems is necessary at every stage of development. To ensure high performance and safety of ADAS and AD, the development of test technology has to happen at least at the same pace to support development. In order to cater to a more realistic testing, Vehicle-in-loop (VIL) methodology integrates a real vehicle into a virtual traffic environment to validate the vehicle’s behaviour. This is both safe and resource efficient. Since it involves both physical/real actors and virtual actors from the simulator, for a timely execution of a test scenario we need a closed loop simulation, with each actor on the test track and simulator being aware of one-another. Closed loop simulation requires updating of trajectories dynamically to each actor based on their dynamic positions to be able to execute a defined traffic scenario. There needs to be synchronized flow of information to and from the actors in real time. In this thesis, we worked on the development of a server on an embedded real time hardware platform. The server is a centralized controller steering test targets along given real time updated trajectories. This server is capable of controlling all the test targets by communicating with them via User Datagram Protocol (UDP) over Wi-fi, in a synchronized manner to provide for a closed loop simulation in real time as a part of VIL. We also studied an existing traffic simulator developed in Simulink and analyzed the different sources of latencies in the system. These latencies lead to scenarios failing to execute in real time due to synchronization errors. As an approach to solving these timing issues, we deployed this simulator onto the same real time platform as the server. The test results showed that the server could steer a Radio Controlled (RC) car in synchronization with the virtual actor generated by the simulator both in open loop and closed loop. Synchronization was achieved by making all the actors refer to a global time stamp and by reducing latencies in the simulator to meet all real time execution constraints.
Keywords: VIL; Closed-loop; Server; Simulator; Real-Time systems; Hardware Platform; UDP